Menilik Urgensi Recordation Oleh Pemegang Hak Kekayaan Intelektual Dalam Sistem Perlindungan Kepabeanan - Khairani, Carel; Utama, Meria; Idris, Akhmad; Irsan, Irsan; Nugraha, Adrian; Nurliyantika, Rizka (JURNAL PERSPEKTIF BEA DAN CUKAI, 2024)
This research explores the urgency of Recordation by intellectual property rights (IPR) holders in the context of customs protection systems. Recordation, as the process of documenting intellectual property rights, plays a crucial role in enforcing IPR protection within the customs environment. The study aims to analyze the effectiveness of Recordation in enhancing IPR protection, identify barriers faced by IPR holders in the Recordation process, and explore its impact on law enforcement and international trade. The research methodology includes policy analysis, case studies, and interviews with relevant stakeholders. The findings of this study are expected to provide in-depth insights into the role of Recordation in optimizing customs protection systems to support IPR holders. The implications of the findings can serve as a foundation for policy enhancements and practices in promoting the effective use of Recordation as a tool to safeguard intellectual property rights on a global scale. Keywords : Recordation, Property Rights, Customs.